Chronology and impact of global research into chronic postoperative pain: a bibliometric analysis of 40 years of research - Guerrero Eraso, Cristian Javier (2024)
Objective: To describe the chronology, evolution and impact of global research into chronic postoperative pain. Materials and methods: A bibliometric study was conducted using the Scopus database. A structured search was designed and validated, thereby allowing the collection of metadata, which were analyzed through the Bibliometrix package of the R programming language. The study involved the description of the general characteristics, evolution and calculation of impact metrics of global research into chronic postoperative pain. Results: The study included 1,496 documents, which spanned from 1983 to 2023. Original articles accounted for 70.7 % (n =1,059) of the total output, followed by reviews (n = 357; 23.8 %). There was an international collaboration rate of 15.6 %, and there has been sustained growth in output since 1983, with a sharp increase in the last 13 years, 2022 being the most prolific one (n =191 published documents). It was identified that Canada and Denmark lead the impact of global research and have the most productive authors and institutions. However, the United States is the most prolific country because it leads significant collaboration, mainly with European and Latin American countries. Neuropathic pain, risk factor assessment and pain management were identified as some of the most frequent topics. Over the past approximately 10 years, there has been persistent interest in research on quality of life, prediction, prevention, and risk factor assessment. Recently, there has been interest in studying pain in video-assisted thoracoscopic surgery and developing predictive models. Conclusions: The study revealed sustained growth in global research on chronic postoperative pain over the past 40 years. Such growth has been mainly led by Canadian and Danish institutions, despite the United States being the most prolific country. Moreover, there has been a significant transition in the studied topics, moving from the use of drugs and identification of risk factors to the study of predictive models, data systematization, and video-assisted surgery.